The Correlation of Interleukin-6, Malnutrition Inflammation Score and Asymmetric Dimethylarginine in Chronic Kidney Disease Patients Undergoing Routine Hemodialysis - Palar, Stella; Wantania, Frans Erwin; Honoris, Hanna (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Chronic kidney disease (CKD) patients undergoing routine hemodialysis (HD) have a high prevalence of protein-energy malnutrition (PEM) and inflammation. The combination of inflammation and PEM is associated with cardiovascular disease and poor outcomes. Interleukin-6 (IL-6) is an inflammatory factor that runs parallel to endothelial damage and is closely related to the nutritional status of CKD HD patients. The tool to assess nutrition status is Malnutrition Inflammation Score (MIS) and to assess endothelial damage is Asymmetric Dimethylarginine (ADMA). It is currently unclear whether there is a correlation between inflammation, malnutrition, and endothelial dysfunction. Therefore the aim of this study is to determine the correlation between IL-6, MIS and ADMA in CKD HD patients. Methods: A cross-sectional design with analytic observational study was conducted on end stage renal disease patient who undergo routine hemodialysis for at least 2 years with the duration of hemodialysis is 4-5 hours and at least twice per week. IL-6 was examined by kit (ELISA) and ADMA using LC-MS/MS at a certified laboratory in Manado city. History taking and physical examination were used to calculate MIS. Data analysis was done using SPSS version 22. Results: There were 30 participants consisting of 22 men (72%) and 8 women (28%). The median age of the subjects was 56.50 years. There was a statistically significant positive correlation between IL-6 and ADMA (r = 0.440, p = 0.015), MIS and ADMA (r = 0.378, p = 0.039), and IL-6 and MIS (r = 0.682, p = 0.0001). Conclusion: There was a significant correlation between IL-6, MIS and ADMA.